The labor market in South Korea, 2000-2016 - Jungmin Lee (IZA World of Labor, 2017)
South Korea has boasted one of the world's most successful economies since the end of World War II. The South Korean labor market has recovered quickly from the depths of the Asian crisis in 1998, and has since remained surprisingly sound and stable. The unemployment rate has remained relatively low, and average real earnings have steadily increased. The South Korean labor market was resilient in the wake of the global financial crisis. However, there are issues that require attention, including high earnings inequality, an aging labor force, increasing part-time jobs, and rising youth unemployment rates.
Keywords: J13; 330; real earnings; unemployment; South Korea